The Organic Intellectual: Theology does not allowed to be chained (2Tm 2,9) - Zanini, Rogério L. (2022)
The text aims to understand the mission of the organic intellectual/theologian with clarity of mission, in the sense of being the bearer of certain values against others, to defend certain interests against others, to take up the cause of the Kingdom of God agains the other anti-kingdoms. According to Ellacuria and Sobrino’s lesson, the poor are the epiphany of Christian revelation and, consequently, of the Christian magisterium, because among the poor God wanted to place his chair. In a limpid and prophetic way, Bishops  explicitly recognized at the Aparecida Conference: “the preferential option for the poor is one of the peculiarities that marks the face of the Latin American and Caribbean Church” (DAp. 391). To address this issue, it is intended to reflect the meaning of a prophetic theology, who descends to the crucified, honoring the reality of the victims of history in view of their resurrection/deliverance. A second aspect follows, in which the mission of Theology is approached as a way of thinking about wounds and rescuing life  for the world to be transformed in the perspective of its Creator; and finally, in the third point, to understand the life and legacy of Father Elli Benincá, an inspiring teacher of the Theology and Pastoral Institute of Passo Fundo-RS, as a case of organic intellectual// theologian. In conclusion, it highlights the importance and topicality/boldness of this method that has the theologian in the position of organic intellectual, because it is,in itself,a prophetic posture in the face of the virtual, individualistic and capitalist reality that marks the 21st Century.